The influence of education on women's well-being: Evidence from Australia. - Dai Binh Tran; Thao Dinh Ngoc Pham; Thuy Thanh Nguyen (PLoS ONE)
This study investigates the relationship between women's education and their level of well-being, using data from the Household, Income and Labor Dynamics in Australia (HILDA). To take into account potential endogeneity, the instrumental variables (IV) approach is employed, with partners' education as an instrument. The findings show that higher education levels lead to a higher level of eudaimonic well-being, hedonic well-being, positive affect, and reduced psychological distress, highlighting a non-monetary benefit of education. Thus, policymakers should continue to widely promote education, in order for women to achieve higher levels of future well-being. Additionally, the findings show that the connection between education and well-being is mediated by healthy behaviors, such as engaging in physical activity, abstaining from drinking and smoking, social interactivity, and higher income. Therefore, public health campaigns which promote healthy behaviors among women should potentially mitigate gaps in formal education.